Tory traditionalism and Christian heritage. Maurice Cowling’s polemics with Friedrich Hayek, John Keynes, and Roger Scruton - Piotrowski, Przemysław (Chrześcijaństwo-Świat-Polityka, 2025)
The Tory traditionalism of the British historian Maurice Cowling appears to be, at its core, a polemic against conservative defeatism. On the other hand, its positive message serves as encouragement to define a conservative option as being in firm opposition to liberalism and in firm support for orthodox and traditional Christianity. These reflections do not seek to address the views that Maurice Cowling criticises. Instead, they primarily aim to try to delineate the specificity of Cowling’s position. Hence, Hayek’s ideological portrait explains why Cowling does not share a sympathy for the term ‘liberal-conservative option’ that is common among conservatives. A sample of Keynes’s views explains Cowling’s lack of illusions about the liberals’ intransigence in relation to the Christian tradition. Cowling’s portrayal of Scruton’s views – Scruton is renowned for his traditionalist stance and staunch opposition to liberalism – is an expression of Cowling’s dislike of the post-romantic quest for a spiritual alternative to allegedly irrevocably defunct Christianity.